Etnotaxonomía de algunas aves nocturnas en el quechua de La Unión - Cancino Verde, Rosalinn Francisca (2019)
Peru is culturally, linguistically and biologically diverse, it is the second country in the world with the greatest diversity of birds, it hosts 1,800 species. Within this context, the research on the etnotaxonomy of some nocturnal birds in the Quechua language of La Unión is intended to give an account of some linguistic processes that operate in the formation of bird names and the influence of the worldview of the speakers of this variant in those processes.